A review on distance measure formula for enhancing match detection process of generic code clone detection model in Java Application - Noormaizzattul Akmaliza, Abdullah; Mohd Azwan, Mohamad Hamza; Al-Fahim, Mubarak Ali (IEEE, 2021)
Two code fragments that are identical to each other and repeatedly being implemented in a software program are called code clones. Code clones are classified into four different type which are clone Type-1, clone Type-2, clone Type3 and clone Type-4. In the past decades, variegated code clone approaches as well as tools have been utilized for detecting code clones. However, the minimum comprehensiveness or lacking of generality in detecting all four types of code clone, has prompted other researchers to develop a code clone detection model. Generic Code Clone Detection (GCCD) Model is the model that implemented a clone detection for the four types of code clone. GCCD incorporates with process namely Pre-processing, Transformation, Parameterization, Categorization and Match Detection process. This research study intends to ameliorate the code clone detection of GCCD Model through Match Detection process of the respective model. A literature review is done to center a few other models and techniques and distance measure formula that available for calculating the code clones in Match Detection process. Based on the analysis, there are ten distance measure formula will be used to decide on the best method for calculating the code clone in Match Detection process. This study hopes to be used as reference for other researchers in aiding their research regarding code clone detection model